Canadian Helicobacter Study Group Consensus Conference: Update on the Approach to Helicobacter Pylori Infection in Children and Adolescents – an Evidence-Based Evaluation. (1st July 2005) - Jones, Nicola L; Sherman, Philip; Fallone, Carlo A; Flook, Nigel; Smaill, Fiona; Veldhuyzen van Zanten, Sander; Hunt, Richard; Thomson, Alan; Canadian Helicobacter Study Group,
Abstract : As an update to previously published recommendations for the management of Helicobacter pylori infection, an evidence-based appraisal of 14 topics was undertaken in a consensus conference sponsored by the Canadian Helicobacter Study Group. The goal was to update guidelines based on the best available evidence using an established and uniform methodology to address and formulate recommendations for each topic. The degree of consensus for each recommendation is also presented. The clinical issues addressed and recommendations made were: population-based screening for H pylori in asymptomatic children to prevent gastric cancer is not warranted; testing for H pylori in children should be considered if there is a family history of gastric cancer; the goal of diagnostic interventions should be to determine the cause of presenting gastrointestinal symptoms and not the presence of H pylori infection; recurrent abdominal pain of childhood is not an indication to test for H pylori infection; H pylori testing is not required in patients with newly diagnosed gastroesophageal reflux disease; H pylori testing may be considered before the use of long-term proton pump inhibitor therapy; testing for H pylori infection should be considered in children with refractory iron deficiency anemia when no other cause has been found; when investigation of pediatric patients with persistent or severe upper abdominal symptoms is indicated, upper endoscopy with biopsy is the investigation of choice; the 13C-urea breath test is currently the best noninvasive diagnostic test for H pylori infection in children; there is currently insufficient evidence to recommend stool antigen tests as acceptable diagnostic tools for H pylori infection; serological antibody tests are not recommended as diagnostic tools for H pylori infection in children; first-line therapy for H pylori infection in children is a twice-daily, triple-drug regimen comprised of a proton pump inhibitor plus two antibiotics (clarithromycin plus amoxicillin or metronidazole); the optimal treatment period for H pylori infection in children is 14 days; and H pylori culture and antibiotic sensitivity testing should be made available to monitor population antibiotic resistance and manage treatment failures.